DEVELOPMENT OF THE SOCIAL SPHERE AND ECONOMIC SYSTEM AS A DETERMINANT OF YOUTH MIGRATORY MOBILITY (ON THE EXAMPLE OF THE CARPATHIAN REGION) - Baranyak, I.; Zherebylo, I. (Socio-economic relations in the digital society, 2021)
The article is devoted to analyses of the state and trends of development of the social sphere and economic system of the Carpathian region. It is generalized that young people, as an active and progressive element of society with a high level of knowledge capitalization, react most dynamically to world trends and are more willing to join migration processes. It is summarized that regional features of demographic development form the theoretical basis of migration potential, while the intensification of migration processes in most cases is due to socio-economic reasons. The analysis of the situation on the youth labor market assesses the density of the relationship between the level of development of the socio-economic system of the Carpathian region and the mobility of young people. Because of the study, multifactor regression equations were constructed, which describe the dependence of the growth rate of external migration processes in the Carpathian region on the variability of socio-economic factors. It is determined that the immigration and emigration vector of mobility of the Carpathian region in socio-economic coordinates depends on the growth rate of average wages, the share of total expenditures of households in the Carpathian region on food, foreign direct investment per capita the Carpathian region and consumer price index. The estimation of volumes of potential external migration of the population in a cut of emigration and immigration vectors in the context of forecast tendencies of social and economic development of areas of the Carpathian region till 2025 is predicted. It is summarized that the intensity of migration processes in working age and the vector of their direction can be a basic factor in establishing demographic and socio-economic security of the Carpathian region. It is proved that the intensity of migration processes of working age and the vector of their direction can be a basic factor in establishing demographic and socio-economic security of the Carpathian region, in case of increased re-emigration and immigration flows or its violation — in case of further leaching of human, mostly age.